Nociception level index as a tool of measuring pain objectively in patients with complex regional pain syndrome: a feasibility study - Umar, Ibrahim; Tenenbaum, Avraham; Tzour, Arik; Khalaia, Amran; Grach, Michael (Frontiers in Pain Research, 2025)
IntroductionThis study evaluates the feasibility of using the Nociception Level Index (NOL) as an objective tool for assessing pain in awake patients with Complex Regional Pain Syndrome (CRPS). Traditional pain assessment methods, such as the Visual Analog Scale (VAS), are subjective and influenced by psychological and cognitive factors, limiting their accuracy in chronic pain conditions.MethodsA single-center, prospective observational study was conducted with 26 CRPS patients. The NOL index, a multi-parameter device measuring autonomic nervous system responses, was assessed alongside VAS scores during physiotherapy exercises and intravenous lidocaine treatment. Pain levels were recorded at baseline, during painful exercises, and post-lidocaine administration. Changes in NOL and VAS scores were analyzed using the Wilcoxon signed-rank test with Bonferroni correction. Receiver operating characteristic (ROC) analysis with bootstrapped 95% confidence interval (CI) evaluated the sensitivity and specificity of NOL and VAS in discriminating painful from non-painful states.ResultsPhysiotherapy exercises significantly increased both NOL (from 22.7 ± 10.7 to 30.3 ± 8.9) and VAS scores (from 5.5 ± 2.8 to 8.15 ± 1.6) (p < 0.001 for both). Lidocaine treatment led to partial pain relief, with VAS scores decreasing statistically significantly (from 7.5 ± 2.2 to 4.7 ± 2.8, p < 0.001), while NOL values trended lower (from 35.3 ± 12.2 to 29.4 ± 15.6, p = 0.26). ROC analysis showed comparable discrimination between painful and non-painful states for both tools [AUC: NOL 0.76 95% CI (0.68,0.84); VAS 0.78 95% CI (0.7,0.85)].ConclusionsThe NOL index shows promise as a complementary tool for objective pain assessment in CRPS, potentially offering insights into pain dynamics that subjective tools may miss. Further research with larger cohorts and standardized protocols is recommended to validate its clinical utility in chronic pain management.